The effect of adjunctive LASER application on periodontal ligament stem cells - Ponnaiyan, Deepa; Rughwani, Roshan R.; Shetty, Ganesh; Mahendra, Jaideep (Frontiers in Cell and Developmental Biology, 2024)
Periodontal regeneration involves the composite action of cell, scaffolds and signaling molecules. There are numerous autologous sources of regenerative cells which are present close to the vicinity of the periodontally debilitated site, the primary one being the periodontal ligament stem cell, which is believed to have a key role in regeneration. Various methods can be harnessed to optimize and enhance the regenerative potential of PDLSCs such as the application of LASERs. In the last few years there have been various studies which have evaluated the effect of different types of LASERs on PDLSCs and the present review summarizes the photo-biomodulative activity of LASERs in general and its beneficial role in the stimulation of PDLSC specifically.